Quality of Paving Block With Additional Ingredients of King Pineapple Leaf Fiber (Agave Cantala Roxb) - Asrial, Asrial; Odang, Hikmah; Mahendra K, Ketut; Selan, Milson; Amidah, Amidah (Journal Research of Social Science, Economics, and Management, 2023)
TThe king pineapple plant (Agave Cantala Roxb) is a plant that grows in lowlands and hills with a stem height between 150-200 cm, and leaf lengths between 90-100 cm, on the inside of the leaves contain a lot of fiber wrapped in green outer ciliates. The quality of paving blocks with additional material of fibers of king pineapple leaves with a size of 2-3 cm, with a percentage of 0%, 3%, 5% and 7% of the weight of cement, in a ratio of 1: 5, then molded with a size of 20 cm x 10 cm x 8 cm. Conducted testing of the tensile strength of single fibers and compressive strength of paving blocks. The results of the takari sand fine aggregate gradation test meet the requirements of SNI 03-1986-1990 in zone III. Specific gravity testing is classified as normal fine aggregates of 2.5 to 2.7 according to SNI 1968-1990. The test results of sludge content of 2.62% ? 5% SK SNI S-04-1989-F, the content weight of 1,550 Kg/cm ? 1.2 Kg/Cm³ refers to the 1989 PBI. Test results Single tensile of king pineapple leaf fibers averaged 196,692 MPa. The weight of the block paving volume decreased by 2.16%, while the absorption of block paving water increased by 0.91%. The test results of the strongest compressive strength of paving blocks are found in additional materials of 5% capable of withstanding a load of 57.56 Kg / cm².